(untitled) (Journal of International Studies, 2020)
This paper attempts to elaborate to what extent cross-border issues such as human rights, political openness, terrorism, economic interdependence, immigrant workers, environment, and separatist movements, caused by globalization influence ASEAN cooperation. Although these issues have not affected greatly cooperation among ASEAN nations, but it is important to note that these issues have influenced the nature of relationship between the state and society, which sometimes disrupts state-to-state relationship within ASEAN. So far, in responding to these new developments, ASEAN members are strict with their main spirit of non-intervention, and leave the problems to individual countries. In contrast to the view that any attempt to solve these assumed domestic issues may raise tension among ASEAN members, this paper argues that such a response is not adequate and that it is by addressing these issues ASEAN may renew the spirit of cooperation and solidarity among its members. ASEAN has been seen as one of the most successful regional organizations in the world outside European Union (Eng 1999: 51; Hass 1989). In spite of the fact that it consists of countries with different ethnic, religious, cultural and political systems, ASEAN remains intact. It has also been able to reduce tension, mitigate security dilemma and make war between its members seem unlikely (Collin 2000: 182). In this regard, Democratic Peace Proposition 1 which argues that relations between democratic states are inherently more peaceful than relations between other regime-types such as democratic versus non-democratic or non-democratic versus non-democratic, has been challenged in the ASEAN case. Different political systems, indeed, make cooperation among countries difficult but it does not necessarily mean that the countries are prone to war.